The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/ico.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Difference Between Corneal and Refractive Astigmatism on LASIK Outcomes Using Solid-State Technology

Abstract: The magnitude of ORA does not seem to be a predictive factor of efficacy and safety of myopic LASIK using a solid-state laser platform. The higher relevance of PCA after surgery in some cases may explain the presence of unexpected astigmatic residual refractive errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…It should be pointed out that the initially obtained good results described above could be achieved without a nomogram and match the previously reported good safety and efficacy profiles reached with solid-state lasers of other research groups [ 17 , 18 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It should be pointed out that the initially obtained good results described above could be achieved without a nomogram and match the previously reported good safety and efficacy profiles reached with solid-state lasers of other research groups [ 17 , 18 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, previously reported characteristics of solid-state laser sources, such as silent operation and the wet ablation process, suggesting a lower susceptibility to corneal hydration, could be reproduced [ 24 , 25 , 26 , 27 , 28 ]. The wet procedure potentially means less thermal stress and consequently less tensile stress in the irradiated tissue, which as an advantage resulting in a faster healing process [ 24 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was reported that the efficacy of LASIK in eyes with a low ORA was twice as good as in eyes with a high ORA 5 . It was also shown that the ORA was strongly correlated with the PCA after LASIK surgery (r = 0.81) 6 . Thus, it is of clinical importance to investigate the PCA distribution in patients having corneal refractive surgery.…”
mentioning
confidence: 92%
“…In the meantime, solid-state laser technology has become a more reliable source for treating organic tissue materials, and the possibility of performing corneal ablation with high efficacy and safety as compared to using an excimer laser is challenging, and has been investigated in experimental studies with good results [ 1 , 2 , 3 , 4 , 5 ]. Since the beginning, corneal refractive surgery with a solid-state laser has been a safe and effective procedure [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Now, growing interest has been noted with the recent presentation of the new platform [ 24 ].…”
Section: Introductionmentioning
confidence: 99%